ANALISIS YURIDIS PENYELESAIAN PEMBIAYAAN BERMASALAH PADA BANK SYARIAH (Studi pada PT. Bank Muamalat Indonesia, Tbk, di kota Medan) - CHRISANTY AMALIA (Universitas Sumatera Utara, 2013)
The presence of syariah bank in Indonesia has long been waited by Indonesian muslim community. The establishment of PT. Bank Muamalat Indonesia, Tbk. in 1991 as the first Syariah bank offers new athmosphere for community’s economy particularly the muslim community. A syariah bank is a bank whose business activities are based on shariah principles. Islamic bank becomes an alternative for community to improve the economy. In providing finance (debt), syariah banks do not apply the system of interest, as a debt interest in Islam which is called riba is unlawful. The bank in seeking for profit does not use interest but money sharing system. Similar to conventional banks, Bank Muamalat provides services such as credit/financing. The forms of financing provided by Bank Muamalat consist of mudharabah, musyarakah, murabahah, salam, istishna, ijarah, ijarah muntahia bitaamlik, or qaradh, qaradh al hasan financing.Financing with the system of installment for certain time includes in murabahah. Murahabah contract is similar to the sale and purchase agreement. So, there is a process of exchange of goods with cash transactions, where payment is carried out within a certain time with a fixed amount of total financing . Keywords: Non Performance Financing, Muamalat Activity, Akad Murabahah